Evaluation of Therapeutic Potential of Platelet Rich Fibrin in the Healing Process of Small Central Tympanic Membrane Perforation using Endoholder (Faridpur Medical College Journal, 2025)
Small central tympanic membrane perforations pose a clinical challenge, often leading to hearing impairment and reduced quality of life. Standard surgical repair may not be feasible for all patients. Platelet Rich Fibrin, an autologous biomaterial rich in growth factors, has emerged as a minimally invasive alternative to enhance healing. This study evaluates Platelet Rich Fibrin, applied via the Endoholder technique, for treating small central tympanic membrane perforations.In this prospective interventional study, 35 patients (mean age: 37.7 ± 15.4 years) with dry, single-sided, small central tympanic membrane perforations were enrolled. Baseline assessments included otoscopy, pure tone audiometry, Weber and Rinne tests, Speech Discrimination Scores, and the Hearing Handicap Inventory for Adults. Platelet Rich Fibrin was prepared through centrifugation of autologous blood and applied to the tympanic membrane using an Endoholder under endoscopic guidance. Follow-up & patient satisfaction was assessed at one month.A 94.3% success rate was observed, with complete tympanic membrane healing in 33 of 35 cases. Pure tone audiometry thresholds improved from 27.6 ± 6.9 dB to 12.3 ± 4.6 dB (p < 0.001), and the air-bone gap reduced from 15.4 ± 7.3 dB to 3.2 ± 1.8 dB (p < 0.001). Speech Discrimination Scores increased from 85.6% to 95.3% (p < 0.01), and Hearing Handicap Inventory for Adults scores improved significantly (14.3 to 1.8, p < 0.001). All patients reported no procedural pain, with a high satisfaction score (28.2/30).Platelet Rich Fibrin, applied endoscopically via the Endoholder, shows promise as a minimally invasive treatment for small TM perforations, warranting further study.Faridpur Med. Coll. J. 2025;20(2):29-34